Large elbow nodules in a patient with rheumatoid nodulosis (Rheumatology Reports, 2010)
Rheumatoid nodulosis is an uncommon pathology considered as a particular variant of rheumatoid arthritis associated with subcutaneous rheumatoid nodules, palindromic rheumatism, and mild or no systemic manifestation, usually with positive rheumatoid factor and radiological subchondral bone cysts. We describe a 58-year-old man with the diagnosis of seropositive but nondestructive, nondeforming rheumatoid arthritis, who exhibits multiple subcutaneous rheumatoid nodules associated with episodes of intermittent arthralgias and subchondral cystic lesions of the small bones of the hands and feet. Large nodules were surgically removed from the two elbows. They were histologically typical of rheumatoid nodules. All these findings were consistent with the diagnosis of rheumatoid nodulosis.